Strategi Komunikasi Persuasif pada Generasi Z Menjelang Pemilihan Presiden 2024 - Weninggalih, Prawiro; Fikriyah, Saniyah Nabila (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2023)
Generation Z is the generation born in 1997-2012, where this generation is considered old enough to take part in democratic parties in Indonesia. As the nation's next generation, Generation Z must be more active in contributing to politics. The current problem is their lack of contribution in this field. Generation Z can be said to be a generation that is literate in technology because it was born in an era where many gadgets or other devices have emerged that make life easier. This generation is the new generation that will take part in elections. Therefore, a good communication strategy is needed so that this generation will increase their knowledge regarding the presidential election. The purpose of this research is to increase the enthusiasm or self-awareness of Generation Z about the importance of voting in the upcoming presidential election. As a result, Generation Z must always be given education, directly or indirectly through the social media they usually use in simple and easy-to-understand language.